Macroprudential Stress-Testing Practices of Central Banks in Central and South Eastern Europe : An Overview and Challenges Ahead - Melecky, Martin; Podpiera, Anca Maria (2012)
Stress tests are the main practical tools of macroprudential oversight. This paper reviews the stress-testing practices of central banks in Central and South Eastern Europe (CSEECBs) and outlines the challenges in the area of stress testing going forward. The authors discuss good practice and the applied approaches by CSEECBs focusing on the main components of a typical macroprudential stress test, i.e. constructing the baseline and stress scenarios, mapping macroeconomic scenarios and microeconomic factors to risk factors, calculating risk exposures to different risk indicators, and estimating outcome indicators to inform macroprudential policy. The main challenges for the CSEECBs going forward involve needed improvements in data reliability, consideration of quantitative microprudential indicators in macroprudential stress tests, explicit incorporation of dynamics in stress tests to include reaction functions of banks and macroprudential policy, institutionalization of macroprudential policy responses to alarming stress-test results, use of the top-down and bottom-up stress test results in supervisory communication, cooperation of macroprudential and microprudential supervision, and information exchange for better cross-border supervision of international banking groups.